Religious Moderation as a Foundation for Social Harmony in the Muslim-Hindu Community of Lingsar, West Lombok - Landrian Landrian (Tabéq: Journal of Local Wisdom, Belief, and Peace, 2026)
This study analyses the role and practical application of religious moderation in fostering social harmony within the multicultural community of Taman Lingsar hamlet, West Lombok Regency. The region is characterised by a significant presence of both Muslim and Hindu adherents who engage closely within shared social and cultural contexts. Employing a qualitative case study approach, data were gathered through participatory observation, in-depth interviews with religious and traditional leaders, village officials, and examination of local documentation. Data analysis utilised Talcott Parsons’ Structural Functionalism theory, specifically the AGIL framework (Adaptation, Goal Attainment, Integration, Latency). The findings demonstrate that religious moderation is operationalised in the daily lives of the Lingsar community through practices of tolerance, respect for theological sensitivities (such as the prohibition of pork in Kemaliq), and interfaith participation. Local traditions, including the Perang Topat and the Kemaliq area, function as integrative spaces that preserve value patterns and unite distinct religious groups while maintaining their theological identities. Ultimately, social harmony in Lingsar is maintained because religious moderation is embedded both culturally and structurally, serving as a mechanism to prevent identity-based conflicts.